Empowerment of Rice Farmers Group Through Training on The Utilization of Rice Straw Waste into Organic Fertilizer - Ningsih, Kustiawati; Sakdiyah, Halimatus; Bachtiar, Da’i (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2025)
The purpose of this program is to increase the knowledge and skills of members of the Harapan Jaya Rice Farmers Group regarding the utilization of rice straw waste into organic fertilizer. The program are in the form of participatory socialization or counseling and training on making organic fertilizer from rice straw waste. The results of the program showed that from a total of 20 participants, 60% considered it very important for socialization and counseling activities and as many as 40% considered it important. The practical activity has an influence on the level of understanding of the participants, which is a significant increase to 3.57 (66,93%). This community service activity is one of the implementations of SDGs, namely climate change mitigation, decent work and economic growth, as well as quality education, so that it can provide business opportunities in the agricultural sector and increase the independence and economy of farmer groups.